Angiotensin-Converting Enzyme Related-Polymorphisms on Inflammation, Muscle and Myocardial Damage After a Marathon Race - Sierra, Ana Paula Rennó; Lima, Giscard Humberto Oliveira; da Silva, Elton Dias; Maciel, Jaqueline Fernanda de Souza; Benetti, Marino Pereira; de Oliveira, Rodrigo Assunção; Martins, Patrícia Fátima de Oliveira; Kiss, Maria Augusta Pedanti; Ghorayeb, Nabil; Newsholme, Philip; Pesquero, João Bosco; Cury-Boaventura, Maria Fernanda (Frontiers in Genetics, 2019)
Muscle damage is one of the most important factors that affect muscle fatigue during endurance exercise. Recent evidence suggests that the renin-angiotensin system impacts on skeletal muscle wasting. The aim of this study was to determine association between the AGT Met235Thr, ACE I/D and BDKRB2 -9/+9 polymorphisms with inflammation, myocardial and muscle injury induced by endurance exercise. Eighty-One Brazilian male runners participated in this study and completed the International Marathon of Sao Paulo. Muscle and myocardial damage markers (alanine transaminase, ALT, aspartate transaminase, AST, lactic dehydrogenase, LDH, creatine kinase, CK, Troponin, pro BNP, myoglobin and CK-MB) and inflammatory mediators (IL-6, IL-8, IL-10, IL12p70, IL1β and TNF-α) were determined one day before, immediately after, one day after, three days after the event. Muscle damage was also determined fifteen days after race and angiotensinogen (AGT) Met235Thr, angiotensin-converting enzyme (ACE) I/D and Bradykinin B2 receptor (BDKRB2) -9/+9 polymorphisms were determined. Marathon race participation induced an increase in all muscle damage and inflammatory markers evaluated (p<0.0001). The muscle damage markers, troponin and pro BNP, CK and LDH and inflammatory markers, IL-6, IL-8, IL-1β and IL-10 were also higher in ACE II genotype immediately after race, compared to DD genotype. The percentage of runners higher responders (>500 U/I) to CK levels was higher for II genotypes (69%) compared to DD and ID genotypes (38% and 40%, respectively) immediately after. Troponin, pro BNP and IL-1β, IL-8 levels were also elevated in AGT MM genotype compared to TT genotype athletes after and/or one day after race. BDKRB2 -9-9 had pronounced response to LDH, CK, CK-MB and ALT and AST activities, myoglobin, troponin, IL-6, IL-8 levels immediately, one day and/or three days after race. The percentage of runners higher responders (>500 U/I) to CK levels was greater for -9-9 and -9+9 genotypes (46 and 48%, respectively) compared to +9+9 genotypes (31%) immediately after. ACE II, AGT MM and BDKRB2 -9-9 genotypes may increase the susceptibility to inflammation, muscle injury after endurance exercise and could be used to predict the development of clinical conditions associated with muscle damage and myocardial injury.